2004
DOI: 10.1016/j.femsim.2004.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Serological and molecular characterization of leptospira serovar Kenya from captive African giant pouched rats (Cricetomys gambianus) from Morogoro Tanzania

Abstract: Two identical leptospiral isolates coded Sh9 and Sh25 obtained from the urine of captive African giant pouched rats (Cricetomys gambianus), destined for use as biodetector of antipersonnel landmines were typed as serovar Kenya using cross-agglutination absorption test and DNA fingerprinting with the insertion element sequences IS1533 and IS1500 derived primers. The two isolates were previously characterized using cultural and serological-microagglutination test as pathogenic leptospires of the serogroup Ballum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 13 publications
4
45
0
2
Order By: Relevance
“…Isolation of Leptospira bacterium is needed for understanding the infecting serovars, which can be included in serodiagnosis of leptospirosis in humans and animals. The reported diversity of reservoir hosts of leptospirosis in Tanzania, namely rodents, bats, domestic animals (Machang'u et al, 1997;Machang'u et al, 2004;Mgode et al, 2006Mgode et al, , 2014 and the present report of Leptospira in fish indicate an urgent need for increasing public awareness of this emerging zoonotic disease in the country. Lack of awareness puts the vulnerable human populations engaged in irrigation farming, fishing, fish farming, livestock keeping and swimming in fresh water at high health risk.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Isolation of Leptospira bacterium is needed for understanding the infecting serovars, which can be included in serodiagnosis of leptospirosis in humans and animals. The reported diversity of reservoir hosts of leptospirosis in Tanzania, namely rodents, bats, domestic animals (Machang'u et al, 1997;Machang'u et al, 2004;Mgode et al, 2006Mgode et al, , 2014 and the present report of Leptospira in fish indicate an urgent need for increasing public awareness of this emerging zoonotic disease in the country. Lack of awareness puts the vulnerable human populations engaged in irrigation farming, fishing, fish farming, livestock keeping and swimming in fresh water at high health risk.…”
Section: Discussionmentioning
confidence: 61%
“…Worker in these environments requires protective gears to prevent infection. Local Leptospira serovars Kenya and Sokoine that are the predominant serovars in rodents and cattle in Tanzania (Machang'u et al, 2004;Mgode et al, 2006) are also the predominant serovars in tilapia and catfish species. This indicates relatedness or sharing of Leptospira pathogens between terrestrial mammals such as rodents and cattle; and aquatic living organisms like fish found in same locality.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that Leptospirosis is a major yet underdiagnosed cause of febrile illness in northern Tanzania. Previous findings in Tanzania (Machang'u et al, 1997(Machang'u et al, , 2003 showed that leptospirosis is much more common than generally thought.…”
Section: Leptospirosismentioning
confidence: 93%
“…A study from Uganda also shows high prevalence of leptospirosis in buffalos (42.39%) and cattle (29.35%) (Atherstone et al, 2013). In Tanzania, several Leptospira serovars including Sokoine, Kenya, Lora, Pomona, Canicola and Hebdomadis have been identified to infect rodents and domestic animals especially in Morogoro (Machang'u et al, 1997;Machang'u et al, 2004;Mgode et al, 2006;Ahmed et al, 2006). A recent report by Biggs et al (2011) also shows a high prevalence of leptospirosis in human patients with fevers in northern Tanzania.…”
Section: Introductionmentioning
confidence: 99%